Amorphous solar modules simulation and experimental results: effect of shading - Melício, Rui (2015)
This paper focuses on the modeling of PV systems by the five parameters model, consisting on a current controlled generator, single-diode, a shunt and series resistances. An assessment for the identification of the parameters is used requiring data on open circuit, maximum power and short circuit tests. A simulation of a photovoltaic system on a parallel of two series connected amorphous solar modules under the effect of partial shading is presented. The estimated parameters are validated by a comparison with experimental measurements on photovoltaic modules.